Educação musical e integração sensorial: abrindo possibilidades de desenvolvimento para crianças autistas - Lenilce da Silva Reis Santana (2023)
Sensory Integration (SI) refers to the way our brain perceives, interprets and issues commands in response to incoming stimuli. Any deregulation in this integration can result in damage to children’s daily activities. Thus, Sensory Integration Dysfunction (DIS) encompasses three distinct disorders, which may be interrelated. Studies indicate a high prevalence of DIS in people diagnosed with Autism Spectrum Disorder (ASD), according to Ayres' Sensory Theory, which suggests a direct link between social integration and learning development. This action-research with mixed approach and exploratory-naturedescriptive study aimed to understand the influence of Music Education on the development of children in Autism Spectrum Disorder and its relationship with Sensorineural Disorder in ten children aged four to six, diagnosed with ASD at level one (1) support in an institution that serves children with the disorder. The study sought to identify the interfaces of this development from the perspective of Sensory Integration, using a mixed method approach that combined quantitative and qualitative methods. Initially, the children were selected and randomly distributed into two groups. The Pilot Group received group, double or individual classes in the second semester of 2022, while the Intervention Group received only individual classes in the first semester of 2023. Both groups were evaluated using the DEMUCA Scale and the ATEC, although the Intervention Group has also been submitted to the Sensory Profile 2. The results indicate a significant development in the areas of music and communication and socialization in both groups. Despite the lack of diagnosis of DIS in children, information provided by parents and observations during classes reveal relevant signs that may be associated with the disorders that make up the DIS. In addition, the Sensory Profile 2 protocol also confirms these observations. Although the numerical results of the ATEC do not present statistical significance, the qualitative analysis suggests improvements in the overall development of children in the Pilot Group. On the other hand, the Intervention Group did not show significant improvements, possibly due to lack of group classes and/or presence of monitors. The DEMUCA Scale, both in qualitative and statistical analyses, indicates significant progress in the musical and general development of children. Regarding the sensory aspects, the results of Sensory Profile 2 indicate evidence of undiagnosed DIS, suggesting the need for reevaluation. Thus, the data qualitatively pointed out a positive relationship for Music Education as a reducer of DIS. As a result of the research, a theoretical-practical training course was given, which enabled the simultaneous implementation of a social project aimed at all children enrolled in the institution. This initiative highlighted the existing gap in the area of Music Education with regard to supporting music educators in Special and/or Inclusive Education contexts. In addition, the positive impact of this training on the personal and professional training of each participant was evidenced, since it was not possible to establish, conclusively, whether or not children have Sensory Integration Dysfunction (DIS) and, consequently, formally stating that music classes had a quantitative impact on the results of the sensory profile in this study was not feasible. However, it is important to note that, in many cases, when children arrived unregulated, they were conducted directly to relaxation activities and, after reaching a state of calm, we started classes, evidence the qualitative impact of music on the behavior and regulation of individuals. Finally, we share some reflections on the essential characteristics that should guide the musical educator, along with suggestions for actions directed to situations of deregulation. In short, the data therefore reinforces the benefits of musical engagement and how music holistically impacts human development. It is noteworthy, however, that to obtain more consistent statistical evidence, it is necessary to expand the sample, being a consideration for future research.